PENINGKATAN LITERASI DIGITAL DAN PENGELOLAAN MEDIA SOSIAL SEBAGAI PENCEGAHAN PENYEBARAN HOAX PADA SISWA/I DI SMA IMMANUEL KOTA BATAM: Digital Literacy Improvement and Social Media Management as Prevention of the Spread of Hoax to Students in Immanuel High School Batam City - Ageng Rara Cindoswari; Angel Purwanti; Andi Maslan; Qori Framana; Stevander Glenn Jeremiah Leong; Liberniat Gea; Auric Auric; Era Azriani (ASOSIASI IDEBAHASA KEPRI, 2023)
The high exposure to information and the rapid circulation of hoax information in Indonesia, especially during the Covid 19 pandemic, indicate the importance of digital literacy education for all parties. Literacy education for students needs to be carried out considering that students are the highest internet users in Indonesia. Literacy education activities are highly recommended to be carried out in formal institutions/organizations or the school environment. SMA Immanuel is one of the educational institutions in the city of Batam that requires assistance regarding digital literacy at SMA Immanuel. This training was carried out to provide (1). Knowledge and understanding of digital literacy and digital security (2). Understanding of hoax news and skills in avoiding the spread of hoax news, and (3). Skills in wise social media management. This coaching method are using lecture, discussion, and practice methods with a duration of 1 hour per session for 4 alternate meetings and is scheduled to involve 7 service members. This coaching is conducted in online meetings using the Zoom application. This coaching will be given to Immanuel school students in the city of Batam, totaling around 10-15 people which will be carried out in the January-June 2022 range. The results of the activity show that there is a significant increase in skills both in digital literacy skills, handling hoaxes, and also social media management.